2001
DOI: 10.1038/sj.sc.3101136
|View full text |Cite
|
Sign up to set email alerts
|

Vital capacity in tetraplegics twenty years and beyond

Abstract: Objectives: To observe the trends in vital capacity (VC) over time in tetraplegics 20 years and more after injury, the e ects of age at injury, severity of injury and gender on this trend. Methods: The medical records of all spinal cord injured persons admitted to a regional spinal injury center from January 1960 to December 1996 were reviewed. Fifty-seven patients had documented post-rehabilitation VC (mean 1.3+1.1 years) and VC at 10 (mean 11.8+2.69) and 20 (20.60+2.67) years post injury and beyond. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In a small series of 12 patients with complete diaphragm paralysis after upper cervical SCI, spontaneous recovery of diaphragmatic activity was seen between 40 and 569 days after SCI, with 7 of the 12 achieving ventilator independence (Oo et al, 1999). In another study, improvement in certain pulmonary function measures were seen as late as 10 years after SCI (Tow et al, 2001), although this finding has not been universally observed (Fugl-Meyer, 1971). …”
Section: Respiratory Recovery After Human Sci: Does Human Plasticimentioning
confidence: 98%
“…In a small series of 12 patients with complete diaphragm paralysis after upper cervical SCI, spontaneous recovery of diaphragmatic activity was seen between 40 and 569 days after SCI, with 7 of the 12 achieving ventilator independence (Oo et al, 1999). In another study, improvement in certain pulmonary function measures were seen as late as 10 years after SCI (Tow et al, 2001), although this finding has not been universally observed (Fugl-Meyer, 1971). …”
Section: Respiratory Recovery After Human Sci: Does Human Plasticimentioning
confidence: 98%
“…Respiratory complications, quality of life and exercise performance Although subjects with SCI have an impaired pulmonary function 3,4,[8][9][10] and are at higher risk for respiratory complications 2,13-15 and mortality, 2,15 only one study 19 reported changes in resting dyspnea. Also in patients with chronic obstructive pulmonary disease RMT already resulted in relieve of dyspnea and improved quality of life.…”
Section: Pulmonary Functionmentioning
confidence: 99%
“…[5][6][7] This results in a decreased efficiency of breathing, a reduction in maximal static respiratory pressures and in reduced pulmonary volumes. 3,4,[8][9][10][11] Moreover, decreased ability to sigh, ineffective coughing and development of mucus hypersecretion will result in inadequate clearance of mucus. 12 All of the foregoing factors contribute to high prevalence of mucus retention, atelectasis, pneumonia and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary function can be followed over time using parameters such as serial vital capacities (VCs) and negative inspiratory forces (NIFs). As an individual ages following an SCI, pulmonary function can be expected to decline, 60 and these parameters can alert the clinician to impending respiratory insufficiency. Parameters can be assessed annually, with the goal of identifying early deterioration in pulmonary function before it becomes clinically urgent.…”
Section: ■ Respiratory Managementmentioning
confidence: 99%